2015
DOI: 10.4049/jimmunol.1402195
|View full text |Cite
|
Sign up to set email alerts
|

Complement Receptor C5aR1/CD88 and Dipeptidyl Peptidase-4/CD26 Define Distinct Hematopoietic Lineages of Dendritic Cells

Abstract: Differential display of the integrins CD103 and CD11b are widely used to distinguish two major dendritic cell (DC) subsets in nonlymphoid tissues. CD103+ DCs arise from fms-like tyrosine kinase receptor 3 (FLT3)-dependent DC precursors (preDC), whereas CD11bhi DCs can arise either from preDCs or FLT3-independent monocytes. Functional characterization of these two lineages of CD11bhi DCs has been hindered by the lack of a widely applicable method to distinguish between them. We performed gene expression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 53 publications
(103 reference statements)
1
60
0
Order By: Relevance
“…To confirm this, we stained lung slices with antibodies against CD103, Sirp1α and CD88. The latter two markers were used to distinguish CD11b + cDCs, which are Sirp1α + CD88 − , from CD88 + macrophages or neutrophils 30 . Using 3D rendering of high power images, we confirmed that both CD103 + and CD11b + cDCs physically interact with Tomato + Th17 cells in the lungs (Figure 6C and Supplementary Videos).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To confirm this, we stained lung slices with antibodies against CD103, Sirp1α and CD88. The latter two markers were used to distinguish CD11b + cDCs, which are Sirp1α + CD88 − , from CD88 + macrophages or neutrophils 30 . Using 3D rendering of high power images, we confirmed that both CD103 + and CD11b + cDCs physically interact with Tomato + Th17 cells in the lungs (Figure 6C and Supplementary Videos).…”
Section: Resultsmentioning
confidence: 99%
“…To determine if high amounts of Th17-promoting cytokines in the two cDC subsets could explain their ability to drive Th17 expansion and production of IL-17 ex vivo , we compared expression of Il23p19 , Il1a , Il1b and Il6 in various lung APCs in a microarray database (http://www.ncbi.nlm.nih.gov/geo/info/linking.html; accession no. GSE64896) 30 . CD11b + cDCs expressed the highest amounts of Il1b RNA (Figure 6E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD11b − DCs express CD8α + in the spleen and CD103 + in nonlymphoid tissues and require IRF8 and BATF3 for their terminal differentiation (19). CD11c + CD11b + MHCII + cells are heterogeneous in nonlymphoid tissues, and the definition of specific DC subsets has only recently been clarified by approaches to separate true CD11b + CD24 + cDC2s from macrophages and monocyte-derived DCs (2022). Because of this diversity, it has been more difficult to discern the transcription factor networks required for terminal differentiation of the cDC2s and other CD11c + CD11b + subsets.…”
Section: Introductionmentioning
confidence: 99%
“…For unknown reasons, however, not all cDCs that acquire inhaled antigens leave the lung, and many of these cells remain in that organ for several months 5,6 . This observation can be partly explained by the developmental ancestry of these cells because monocyte-derived CD11c + cells lacking the chemokine receptor, CCR7, are unable to migrate to regional LNs 7,8 . It seems likely that the migration potential of cDCs is also determined, at least in part, by their anatomical position within the lung.…”
Section: Introductionmentioning
confidence: 99%